A Rasch Analysis of the Zarit Burden Interview (ZBI) Scale Among Tsunami Survivors’ Caregivers - Sari, Novita; Julianto, Very; Kamsi, Kamsi; Liem, Andrian; Ummah, Izzatul (Jurnal Psikologi, 2026)
This study aimed to validate the Zarit Burden Interview (ZBI) among caregivers of elderly tsunami survivors in Aceh,Indonesia. In contexts characterized by disasters or significant social disruption, such as the aftermath of a tsunami, the burden on caregivers becomes increasingly critical. This phenomenon is due to the compounded vulnerabilities experienced by elderly tsunami survivors, which arise from trauma, displacement, and weakened community support systems. Therefore, it is imperative to validate the ZBI (Zarit Burden Interview) in this context. Using the Rasch Model, the study included 513 participants and assessed the construct validity of the ZBI. The findings indicated that the ZBI had a high internal consistency (person separation reliability = 0.81). In dimensionality measurement, an unexplained variance in the 1st contrast of 2.6 was found, slightly above the threshold, suggesting multidimensionality. However, with raw variance explained exceeding 40% and approaching 60%, the instrument can be considered sufficiently unidimensional. However, item 21 was identified as a misfit. Thus, it requires revision, considering local cultural values. Overall, the validation of the ZBI using the Rasch model resulted in an instrument that is valid and applicable to post-disaster contexts.